An alternative low-cost adsorbent for gold recovery from cyanide-leached liquors: Adsorption isotherm and kinetic studies - Refiloe Tsolele; Fanyana Moses Mtunzi; Michael John Klink; Vusumzi Emmanuel Pakade (Adsorption Science & Technology)
Pristine Macadamia nutshell-based activated carbons were chemically oxidized with different concentrations of H 3 PO 4 and HNO 3 to increase their surface adsorption properties and further explore if they could be an attractive alternative low-cost adsorbent for gold recovery from cyanide-leached liquors. The modified activated carbons were labeled MACN 20 , MACN 40 and MACN 55 to signify the materials prepared from 20%, 40% and 55% (v/v) HNO 3 , respectively. Similar nomenclature was followed for H 3 PO 4 -modified activated carbons. Brunauer-Emmet-Teller, scanning electron microscopy, thermogravimetric analysis, Fourier transform infrared spectroscopy, elemental analysis and X-ray diffraction spectroscopy were used to characterize the prepared activated carbons. The physical properties were attained through determining attrition, ash content, volatile matter and moisture content of all the activated carbons. Various parameters that affect selective adsorption such as the effect of initial concentration, time, agitation speed, interfering species and the dose of the adsorbent were investigated. Optimal parameters for gold ion adsorption were as follows: solution pH, 10; contact time, 6 h; agitation speed, 150 r/min; sorbent amount, 4 g and initial concentration, 5.5 mg/L. The observed selectivity order was not the same for all the adsorbents, but the adsorption of gold was found to be mostly influenced in the presence of nickel and least influenced by copper. MACN 55 was found to be the most efficient adsorbent with 74% of gold adsorption from a real-world sample and displayed a similar performance to coconut-based activated carbons.